Analyzing the Cyberspace Laws to Protect Data Privacy in Pakistan - Zahoor, Rashida; Razi, Naseem (Law, State and Telecommunications Review, 2021)
[Purpose] Cyberspace technology has become an unavoidable forum for communications, connections, and transactions. This phenomenon, however, led to cybercrimes and hi-tech crimes such as data leaking, stealing, blackmailing, digital fraud, bullying and hacking, and all this has put the cyberspace technology at risk and a great threat to the security and privacy of the people. In Pakistan, cybercrimes are on the rise and despite several laws had been published on the topic, the rate of cybercrimes is increasing every passing year. In this context, this study examines the existing regulatory and legal framework for data protection in Pakistan and to find out the major challenges in the way of application and enforcement mechanism. [Methodology] The conceptual framework of the research answers the question on to what extent the existing laws and enforcement mechanism of Pakistan is effective in protecting the data and information in the cyberspace? It highlights the importance of cyberspace technology nowadays and addresses the global agenda to combat cybercrimes, analyzes the Pakistani laws on the protection of data and privacy in cyberspace, and identifies major challenges in the way of the enforcement mechanism. The study focuses on the cyberspace laws of Pakistan with reference to the cybercrimes from a national perspective. [Findings] This paper asserts that there is sufficient protection of cyberspace laws in Pakistan although they lack proper enforcement and are plagued with poor management.